Introduction to the Special Issue on Expressions of Information and Communication Theory and Practice - Fomin, Vladislav; Grigas, Vincas (Information & Media, 2023)
This paper provides an introduction to the special issue on expressions of information and communication theory and practice. It surveys each paper, identifies commonalities and dissimilarities among them, and suggests the potential readership for the papers based on the problems addressed and the findings.
Keywords: identity; knowledge sharing; virtual communities; sustainable fashion; internal communication